PENINGKATAN LITERASI BACA DENGAN SIMAK BACA PAGI SISWA KELAS III DI SEKOLAH DASAR NEGERI MUNGUP - Pristiawati, Eva Abripda (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2023)
ABTRACTThis study aims to determine literacy strategies in increasing students' interest in reading, as well as the supporting and inhibiting factors. In addition, it also aims to determine the role of literacy, obstacles and efforts made in schools in increasing students' interest in reading in elementary schools. The method used is the technique of data collection in the form of data collection techniques, interview techniques, and document or documentation study techniques. The results of this study indicate that increasing reading literacy by listening to reading for third grade students of SD Negeri Mungup is carried out in various ways so that students can enjoy reading more. One of the efforts made is by carrying out literacy habits by listening to reading in the morning 15 minutes before learning begins and creating a reading corner in the corner of the classroom. After the implementation of these efforts then carried out data checking. The results of these data show that most of the Mungup Public Elementary School students are interested in reading both story books and textbooks. Literacy activities need to be habituated and also with the approval of parents. There are morning reading activities carried out by the teacher as a guide for students who take turns reading books for 15 minutes before learning begins with reading books such as story books or textbooks in the class reading corner. This teaches students to love or like to do reading activities.Keywords: Literacy, Interest in reading, Elementary School, Students